Comparative Growth and Yield of Seedling Origin Crop and First Coppice Crop in Eucalyptus Hybrid - Prasad, Ram (Indian Forester, 1989)
Sample plot data pertaining to seedling origin crop and first coppice crop of Eucalyptus hybrid, E. tereticornis and E. camaldulensis have been analysed. This study have shown that growth and yield from coppice crop is 2 to 3 times higher than the seedling crop of the same age. The results of the analysis have been reported in this paper.